Investigations on the dependence of the stability threshold on different operating procedures in a single-phase rectangular natural circulation loop. (November 2020) - Elton, D.N.; Arunachala, U.C.; Vijayan, P.K.
Highlights: Systematic stability experiments in a uniform diameter rectangular loop were carried out with a diameter larger than previously reported studies. Since the loop was almost entirely unstable with ambient temperature coolant, chilled water was used in the cooler to enhance the stability threshold. The existence of a hysteresis region where the stability threshold depends on the operating procedure has been confirmed. The existence of different regions like unconditionally stable, conditionally stable, and unconditionally unstable have been confirmed. In contrast to previous studies in smaller diameter loops, periodic oscillations were not observed in the present loop and all observed oscillations were chaotic in nature. Abstract: During the past years, several studies were focused on the instability of single-phase rectangular natural circulation systems. However, experimental identification of instability threshold and categorization of instability regimes is of prime interest in many industrial applications which have been addressed by very few researchers that too limited to lower diameter loops only. Hence, in the present study, a larger diameter rectangular loop with horizontal heater horizontal cooler (HHHC) configuration has been designed to generate single phase natural circulation data on the steady state and stability behavior. Effect of different operating procedures (i.e., start-up from rest, power raising from stable steady state, and power reduction from an unstable state) on stability behavior are studied. Most of the oscillatory regimes are identified and noticed that the operating procedure can influence the instability threshold. The instability threshold was found to increase with the lowering of the coolant temperature and increasing its flow rate. The operating procedures i.e., power raising from stable steady state and start-up from rest gave the maximum and minimum values of the stability threshold respectively. As opposed to this, the minimum instability threshold in smaller diameter loops was reported for the operating procedure with power reduction from an unstable state. The experimental results confirm the occurrence of the hysteresis phenomenon. Due to the larger diameter and lower Lt /D ratio of the loop, all the oscillatory behaviors were aperiodic in nature in contrast to the observations in smaller diameter loops.